Dinamika Implementasi Pemenuhan Hak Terhadap Buruh Cacat Akibat Kecelakaan Kerja - Aurael Filvensha Insyilla; Bellmiro Umara Bahsora; Elsa Eka Julia Putri; Fairuzah Meeya Basyarah (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the implementation of laws and regulations regarding the fulfillment of the rights of workers with disabilities resulting from workplace accidents, as well as the penalties imposed on companies that fail to fulfill these rights. The state has guaranteed the right to work and fair treatment for every citizen, including persons with disabilities, through the 1945 Constitution of the Republic of Indonesia, Law No. 8 of 2016, the Labor Law, and other implementing regulations. However, in practice, there remains a gap between legal norms and their implementation, as seen in the case of Giri Pamungkas, who suffered a permanent disability due to a work-related accident but still faced termination of employment and did not receive optimal post-accident protection. This study employs a normative legal method with a qualitative-descriptive approach. The results of the study indicate that workers who suffer disabilities due to work-related accidents remain entitled to employment protection, wages, healthcare, adequate accommodation, rehabilitation, and a prohibition on termination of employment until their recovery is confirmed. Companies that fail to fulfill these rights may be subject to administrative and criminal sanctions, as well as obligations to pay compensation, severance pay, and benefits in accordance with applicable legal provisions.